Mobile and personal communication systems and services - Pandya, Raj (New Delhi : Prentice Hall of India, 2004)
Engineering
Keywords: Mobile communication; Cellular concept; Digital cellular mobile systems; Wireless communication; Mobile data communication; IMT-2000; Third generation mobile communication; Universal mobile telecommunication